Examining Students’ and Perceived Teachers’ Attitudes towards Soft Skills’ Integration in Master’s Programs: A Quantitative Study - Aboulghazi, Maryam (International Journal of Language and Literary Studies, 2026)
Moroccan higher education institutions are expected to realign their objectives and implement updated pedagogical practices that promote the inclusion of soft skills. Nevertheless, the actual implementation of these skills continues to face difficulties and sparks considerable debate. This research aims to examine students’ and perceived teachers’ attitudes towards soft skills’ integration within Moroccan master’s programs of English department and explores the differences between them. To achieve these objectives, a cross-sectional design was employed; quantitative data was collected from 208 master students through the use of questionnaires. The findings indicate that students hold positive attitudes towards the integration of soft skills, whereas professors are perceived as moderately enthusiastic and constrained by practical course limitations. The results of the paired test illustrate a statistically significant difference between students’ and perceived teachers’ attitudes, with a p-value less than 0.001. Therefore, the findings of this study would imply a need for a balanced integration of cognitive and social skills, namely the practical engagement of those skills through the use of innovative approaches and methods.